Pengalaman Ibu dalam Merawat Bayi Preterm yang Pernah Dirawat di Ruang Neonatus Intensive Care Unit Kota Bengkulu - Padila Padila; Muhammad Amin; Rizki Rizki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to explore the experience of mothers in caring for preterm babies who had been treated in the NICU room in Bengkulu City. This type of research is a qualitative research with a phenomenological approach. The results of the study were 6 (six) themes produced, namely the description of mothers about babies born preterm and their characteristics, etiology or causes of preterm, the experience of preterm baby care after returning from hospital, support obtained by mothers during the care of preterm infants, maternal coping mechanisms in caring for a preterm baby, and the mother's reaction while caring for her preterm baby. The conclusion of this study is the mother's experience in caring for preterm babies who have been treated in the NICU room in Bengkulu City. Keywords: Phenomenology, Mother's Experience, Preterm